Habib Ja'far's Digital Da'wah Strategy on Youtube: Inspiring Through the Log In Theme - Fadilah, Nurul; Lutfiaturrahma Alhaq , Dinda; Trizuwani , Siti; Balqis , Ratu (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
There has been no specific research on Habib Jafar's digital da'wah strategy on YouTube with the theme Login, even though the content has reached 14 million viewers. This research is important to understand the strategy of da'wah on social media, especially YouTube. The objectives of this study are 1) How is the Implementation of Habib Jafar's Digital Da'wah Strategy on Youtube with the Login Theme; 2) What are the Factors Affecting Youtube Content with the Login Theme Achieving High Viewrs. The research method used in this research uses the library method with primary data from Habib Jafar's YouTube content, especially the episode “Religion Many Prohibitions Mending Follow Satan?”. Secondary data is obtained from books, journals, and online sources. Data collection techniques were carried out through observation of content elements and documentation of scenes, discussions, and interviews in the video. The results of this study show that Habib Jafar utilizes YouTube as an effective da'wah platform, adapting media ecology theory to deliver messages with an approach that is relevant and familiar to the younger generation. Through a relaxed style, slang, humor, and inviting figures from various backgrounds, he succeeded in opening a space for discussion and providing a broader understanding of Islam. YouTube algorithm optimization, such as the use of the right keywords, interesting descriptions, consistency of uploads, and interaction with the audience, also increases the number of viewers. Content that raises social issues and changes people's views.